Metal and non-metallic element co-doped high-entropy sulfide solid electrolyte
Through the high-entropy sulfide solid electrolyte co-doped with metal and non-metal elements, the problems of high price and poor stability of existing sulfide electrolytes are solved, and the high ionic conductivity and air stability are improved, which is suitable for high energy density and high safety battery applications.
Patent Information
- Application Number
- CN202411714592.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Existing high ionic conductivity sulfide solid electrolytes are expensive and easy to dehydrate, with poor air stability and interface stability, which limits the application of sulfide solid electrolytes.
Using high-entropy sulfide solid electrolyte co-doped with metal and non-metal elements, the preparation method includes water-free and air-free The precursor is mixed under a protective atmosphere of oxygen, ball milled and sintered to obtain a powdered electrolyte.
It significantly improves the ionic conductivity and air stability of the sulfide electrolyte, improves the room temperature ionic conductivity of the electrolyte, and is theoretically suitable for manufacturing secondary batteries with high safety performance and high specific energy.
Smart Images

Figure CN119297385A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage batteries, and more specifically, to a high-entropy sulfide solid electrolyte co-doped with metal and non-metal elements, and a preparation method and application thereof. Background Art
[0002] Traditional lithium-ion batteries rely on liquid electrolytes to conduct lithium ions. Although they have achieved great commercial success, their inherent safety risks and energy density limitations make them challenging in high-energy storage and high-safety application scenarios. At the same time, all-solid-state lithium-ion batteries have the potential to break through the bottleneck of electrochemical energy storage and meet future development needs due to their advantages such as high safety and high energy density, attracting people's attention.
[0003] Among them, sulfide solid-state lithium battery is a cutting-edge energy storage technology. Due to its advantages such as high energy density, high safety and long cycle life, it is becoming an important research direction for the next generation of lithium-ion batteries. Compared with traditional liquid lithium-ion batteries, sulfide solid-state batteries use solid electrolytes, which can effectively solve safety problems such as leakage, thermal runaway and battery explosion caused by liquid electrolytes. However, the existing sulfide solid electrolytes with high ionic conductivity are very expensive and easy to deliquesce; the disadvantages such as poor air stability and interface stability limit the application of sulfide solid electrolytes. Therefore, the existing technology still needs further improvement and development. Summary of the invention
[0004] In view of the above reasons, the purpose of the present invention is to provide a high entropy sulfide solid electrolyte co-doped with metal and non-metal elements, and its preparation method and application. The high entropy sulfide solid co-doped with metal and non-metal elements provided by the present invention can effectively adjust the disorder, reduce the lithium ion diffusion barrier, and greatly improve the lithium conductivity and air stability. The present invention provides a sulfide solid electrolyte co-doped with metal and non-metal elements. The chemical formula of the sulfide solid electrolyte co-doped with metal and non-metal elements is: Li 10+a-b-c Na b X c M 1-d Q d Te e O f P2S 12-e-f-g Z g, X is K, Mg, Ca, Al, Fe or Zn; M is one or more of Ge, Sn, Si; Q is at least one of Sb, Bi, As, Y, La; Z is at least one of F, Cl, Br, I; where 0 < b ≤ 3, 0 ≤ c ≤ 1, 0 ≤ d < 1, 0 < e ≤ 2, 0 < f ≤ 1, 0 < g ≤ 3; when the valence of element X is +1, a = 2e + d - g; when the valence of element X is +2, a = 2e + d - c - g; when the valence of element X is +3, a = 2e + d - 2c - g.
[0005] Preferably, the sulfide solid electrolyte co-doped with metal and non-metal elements is in powder form.
[0006] Preferably, the particle size of the sulfide solid electrolyte co-doped with metal and non-metal elements is 1 nm - 100 μm.
[0007] According to another aspect of the present invention, there is provided a method for preparing the sulfide solid electrolyte co-doped with metal and non-metal elements according to any one of the above, comprising the following steps:
[0008] Under an anhydrous and oxygen-free protective atmosphere, mix the precursors Li2S, LiZ, Na2S, MTe, XZ x , MS2, QZ3, P2S5, P2O5, perform ball milling, then press into pellets and sinter to obtain the sulfide solid electrolyte Li 10+a-b-c Na b X c M 1-d Q d Te e O f P2S 12-e-f-g Z g , X is K, Mg, Ca, Al, Fe or Zn; M is one or more of Ge, Sn, Si; Q is at least one of Sb, Bi, As, Y, La; Z is at least one of F, Cl, Br, I; where, 0 < b ≤ 3, 0 ≤ c ≤ 1, 0 ≤ d < 1, 0 < e ≤ 2, 0 < f ≤ 1, 0 < g ≤ 3; x is the valence of element X; when x = 1, a = 2e + d - g; when x = 2, a = 2e + d - c - g; when x = 3, a = 2e + d - 2c - g.
[0009] Preferably, the protective atmosphere is argon.
[0010] Preferably, the mass ratio of balls to materials in the ball milling is 5:1 - 200:1.
[0011] Preferably, the rotation speed of the ball milling is 100 - 2000 rpm, and the time of the ball milling is 1 - 48 h.
[0012] According to another aspect of the present invention, there is provided an all-solid-state battery comprising the sulfide solid electrolyte co-doped with the metal and non-metallic elements as described in any one of the items.
[0013] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0014] (1) The present invention provides a high entropy sulfide solid electrolyte co-doped with metal and non-metal elements and its preparation method and application. The ionic conductivity of conventional sulfide solid electrolytes is about 1×10 -2 S cm -1 The present invention significantly improves the configuration entropy and disorder of the material by doping a variety of metal and non-metal elements, O elements and halogen elements of suitable types, ion radii and proportions, reduces the energy barrier for lithium ion diffusion, and thus improves the ionic conductivity of the sulfide electrolyte.
[0015] (2) After the oxygen atom is doped in the present invention, the system introduces non-bridging bond O. In comparison, non-bridging bond O is more stable than bridging bond S, thereby improving the air stability of the electrolyte. The introduction of low electronegativity cationic elements effectively inhibits electronic conductivity and enhances the ability of the electrolyte to resist the growth of lithium dendrites.
[0016] (3) The introduction of multiple anions in the present invention can generate lithium halide in situ during the electrochemical reaction, thereby improving the stability of the electrolyte and the positive electrode interface. The high entropy sulfide solid electrolyte provided has a high ionic conductivity, and its room temperature ionic conductivity can reach 3.5×10 -2 S cm -1 The above can theoretically be applied to manufacture secondary batteries with high safety performance and high specific energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The present invention is based on the Li prepared in Example 1 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0. 3O 0.6 SEM image of .
[0018] Figure 2 The Li prepared in Example 1-3 of the present invention 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3O 0.6 , Li 9.8 Na 0.1 Si 0.5 Ge 0.4 Sb 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 , Li 9.8 Na 0.1 Si 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 XRD pattern of .
[0019] Figure 3 The Li prepared in Example 1 and Example 3 of the present invention is 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 , Li 9.8 Na 0.1 Si 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 Electrochemical impedance spectroscopy.
[0020] Figure 4 The present invention is based on the Li prepared in Example 1 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0. 3O 0.6 The first charge-discharge cycle voltage curve of the all-solid-state battery prepared with solid electrolyte.
[0021] Figure 5 The present invention is based on the Li prepared in Example 1 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0. 3O0.6 Electronic impedance spectrum. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0023] Example 1
[0024] This embodiment provides a high entropy sulfide solid electrolyte Li co-doped with metal and non-metal elements. 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 , the specific preparation method is as follows:
[0025] In an Ar atmosphere glove box, weigh Li2S, Na2S, Al2S3, GeS2, SiS in molar ratio. 2、 Bi2S3、P2S 5、 P2O5, SnTe, LiBr precursor powders were placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powders were added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 50:1; the ball mill was transferred to a ball mill, and the mixture was ball milled at 500 rpm for 30 hours, and then cooled to room temperature naturally. The mixture was cold pressed into a 10 mm diameter disc, sealed in a quartz tube, and heat treated at 500 ° C in a muffle furnace for 8 hours. Finally, the heat-treated ceramic sheet was ground into powder to obtain the final Li 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 Solid electrolyte powder. All operations were carried out under argon protection, and the water partial pressure and oxygen partial pressure were guaranteed to be less than 1ppm. 7.9 Na3AlSi 0.6 Ge 0. 3Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O0.6 High entropy sulfide solid electrolyte. The ionic conductivity of this electrolyte is 2.54×10 -2 Scm -1 .
[0026] Figure 1 The present invention is based on the Li prepared in Example 1 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0. 3O 0.6 SEM image of .
[0027] Figure 2 The Li prepared in Example 1-3 of the present invention 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0. 3O 0.6 , Li 9.8 Na 0.1 Si 0.5 Ge 0.4 Sb 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 , Li 9.35 Na 0.1 Si 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 XRD pattern of .
[0028] Figure 3 The Li prepared in Example 1 and Example 3 of the present invention is 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 , Li 9.35 Na 0.1 Si 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S11.05 Cl 0.3 O 0.6 Electrochemical impedance spectroscopy.
[0029] Figure 4 The present invention is based on the Li prepared in Example 1 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0. 3O 0.6 The first charge-discharge cycle voltage curve of the all-solid-state battery prepared with solid electrolyte.
[0030] Figure 5 The present invention is based on the Li prepared in Example 1 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0. 3O 0.6 Electronic impedance spectrum.
[0031] Example 2
[0032] This embodiment provides a high entropy sulfide solid electrolyte Li co-doped with metal and non-metal elements. 9.8 Na 0.1 Si 0.5 Ge 0.4 Sb 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 , the specific preparation method is as follows:
[0033] In an Ar atmosphere glove box, weigh Li2S, Na2S, GeS2, SiS in molar ratio. 2、 Sb2S3、P2S 5、 P2O5, SnTe, and LiCl precursor powders were placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powders were added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 50:1; the ball mill was transferred to a ball mill, and the mixture was ball milled at 800 rpm for 30 hours, and then cooled to room temperature naturally. The mixture was cold pressed into a 10 mm diameter disc, sealed in a quartz tube, and heat treated at 700 ° C in a muffle furnace for 8 hours. Finally, the heat-treated ceramic sheet was ground into powder to obtain the final Li 9.8 Na 0.1 Si0.5 Ge 0.4 Sb 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 Solid electrolyte powder. All operations were carried out under argon protection, and the water partial pressure and oxygen partial pressure were guaranteed to be less than 1ppm. 9.8 Na 0.1 Si 0.5 Ge 0.4 Sb 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 High entropy sulfide solid electrolyte. The ionic conductivity of this electrolyte is 2.1×10 -2 S cm -1 .
[0034] Example 3
[0035] This embodiment provides a high entropy sulfide solid electrolyte Li co-doped with metal and non-metal elements. 9.8 Na 0.1 Si 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 , the specific preparation method is as follows:
[0036] In an Ar atmosphere glove box, weigh Li2S, Na2S, Al2S3, GeS2, SiS in molar ratio. 2、 Bi2S3、P2S 5、 P2O5, SnTe, and LiCl precursor powders were placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powders were added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 50:1; the ball mill was transferred to a ball mill, and the mixture was ball milled at 800 rpm for 30 hours, and then cooled to room temperature naturally. The mixture was cold pressed into a 10 mm diameter disc, sealed in a quartz tube, and heat treated at 700 ° C in a muffle furnace for 8 hours. Finally, the heat-treated ceramic sheet was ground into powder to obtain the final Li 9.8 Na 0.1 Si 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6Solid electrolyte powder. All operations were carried out under argon protection, and the water partial pressure and oxygen partial pressure were guaranteed to be less than 1ppm. 9.8 Na 0.1 Si 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 High entropy sulfide solid electrolyte. The ionic conductivity of this electrolyte is 1.85×10 -2 Scm-1.
[0037] Example 4
[0038] This embodiment provides a high entropy sulfide solid electrolyte Li co-doped with metal and non-metal elements. 9.8 Na 0.1 Si 0.5 Ge 0.4 As 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 , the specific preparation method is as follows:
[0039] In an Ar atmosphere glove box, weigh Li2S, Na2S, GeS2, SiS2, As2S3, P2S in molar ratio. 5、 P2O5, SnTe, LiBr precursor powders were placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powders were added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 50:1; the ball mill was transferred to a ball mill, and the mixture was ball milled at 800 rpm for 30 hours, and then cooled to room temperature naturally. The mixture was cold pressed into a 10 mm diameter disc, sealed in a quartz tube, and heat treated at 700 ° C in a muffle furnace for 8 hours. Finally, the heat-treated ceramic sheet was ground into powder to obtain the final Li 9.8 Na 0.1 Si 0.5 Ge 0.4 As 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 Solid electrolyte powder. All operations were carried out under argon protection, and the water partial pressure and oxygen partial pressure were guaranteed to be less than 1ppm. 9.8 Na 0.1 Si 0.5 Ge 0.4 As 0.1 Te0.05 P2S 11.05 Br 0.3 O 0.6 High entropy sulfide solid electrolyte. The ionic conductivity of this electrolyte is 2.52×10 -2 S cm -1
[0040] Example 5
[0041] This embodiment provides a high entropy sulfide solid electrolyte Li co-doped with metal and non-metal elements. 11.1 Na 0.1 Al 0.15 Si 0.6 Ge 0.3 Bi 0.1 Te2P2S5F3O, the specific preparation method is as follows:
[0042] In an Ar atmosphere glove box, weigh Li2S, Na2S, Al2S3, GeS2, SiS in molar ratio. 2、 Bi2S3、P2S 5、 P2O5, SnTe, and LiF precursor powders were placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powders were added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 50:1; the ball mill was transferred to a ball mill, and the mixture was ball milled at 800 rpm for 30 hours, and then cooled to room temperature naturally. The mixture was cold pressed into a 10 mm diameter disc, sealed in a quartz tube, and heat treated at 700 ° C in a muffle furnace for 8 hours. Finally, the heat-treated ceramic sheet was ground into powder to obtain the final Li 11.1 Na 0.1 Al 0.15 Si 0.6 Ge 0.3 Bi 0.1 Te2P2S5F3O solid electrolyte powder. All operations were carried out under argon protection, and the water partial pressure and oxygen partial pressure were guaranteed to be less than 1ppm. 11.1 Na 0.1 Al 0.15 Si 0.6 Ge 0. 3Bi 0.1 Te2P2S5F3O high entropy sulfide solid electrolyte. The ionic conductivity of the electrolyte is 3.5×10 -2 S cm -1
[0043] Example 6
[0044] This embodiment provides a high entropy sulfide solid electrolyte Li co-doped with metal and non-metal elements.9.8 Na 0.1 SiTe 0.05 P2S 11.05 Br 0.3 O 0.6 , the specific preparation method is as follows:
[0045] Weigh Li2S, Na2S, SiS2, and P2S in molar ratio in an Ar atmosphere glove box. 5、 P2O5, SnTe, LiBr precursor powders were placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powders were added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 50:1; the ball mill was transferred to a ball mill, and the mixture was ball milled at 800 rpm for 30 hours, and then cooled to room temperature naturally. The mixture was cold pressed into a 10 mm diameter disc, sealed in a quartz tube, and heat treated at 700 ° C in a muffle furnace for 8 hours. Finally, the heat-treated ceramic sheet was ground into powder to obtain the final Li 9.8 Na 0.1 SiTe 0.05 P2S 11.05 Br 0.3 O 0.6 Solid electrolyte powder. All operations were carried out under argon protection, and the water partial pressure and oxygen partial pressure were guaranteed to be less than 1ppm. 9.8 Na 0.1 SiTe 0.05 P2S 11.05 Br 0.3 O 0.6 High entropy sulfide solid electrolyte. The ionic conductivity of this electrolyte is 2.12×10 -2 S cm -1 .
[0046] Example 7
[0047] This embodiment provides a high entropy sulfide solid electrolyte Li co-doped with metal and non-metal elements. 9.8 Na 0.1 Sn 0.9 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 , the specific preparation method is as follows:
[0048] Li2S, Na2S, SnS were weighed in molar ratio in an Ar atmosphere glove box. 2、 Bi2S3、P2S 5、P2O5, SnTe, LiBr precursor powders were placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powders were added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 50:1; the ball mill was transferred to a ball mill, and the mixture was ball milled at 800 rpm for 30 hours, and then cooled to room temperature naturally. The mixture was cold pressed into a 10 mm diameter disc, sealed in a quartz tube, and heat treated at 700 ° C in a muffle furnace for 8 hours. Finally, the heat-treated ceramic sheet was ground into powder to obtain the final Li 9. 8Na 0.1 Sn 0.9 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 Solid electrolyte powder. All operations were carried out under argon protection, and the water partial pressure and oxygen partial pressure were guaranteed to be less than 1ppm. 9.8 Na 0.1 Sn 0.9 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 High entropy sulfide solid electrolyte. The ionic conductivity of this electrolyte is 2.24×10 -2 S cm -1 .
[0049] Performance Testing
[0050] Weigh 150 mg of electrolyte powder and place it in a special solid-state battery mold with a diameter of 10 mm. Press it at a pressure of 350 MP and perform AC impedance spectrum test. The ionic conductivity of the sulfide solid electrolyte is calculated based on the impedance value and the Arrhenius formula. The calculation results are shown in Table 1. At the same time, the configuration entropy of the chemical formula is calculated based on the thermodynamic formula and is shown in Table 1. The electronic conductivity of the sample is tested by direct current polarization (DC). The test voltage range is 0.1 V, and the polarization time for each test is 60 min. The test results are shown in Figure 5 .
[0051] like Figure 3 As shown, the sample Li obtained in Example 1 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 The ionic conductivity can reach 2.54×10 -2 S cm-1 .
[0052] like Figure 3 As shown, the sample Li obtained in Example 3 9.8 Na 0.1 Si 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Cl 0.3 O 0.6 The ionic conductivity can reach 1.85×10 -2 S cm -1 .
[0053] like Figure 4 As shown, the Li obtained in Example 1 is used 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 The full battery is assembled with LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode; Li 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 As electrolyte; Li-In alloy as negative electrode, charge and discharge tests were carried out at a rate of 0.1C.
[0054] like Figure 5 As shown, the sample Li obtained in Example 1 7.9 Na3AlSi 0.6 Ge 0.3 Bi 0.1 Te 0.05 P2S 11.05 Br 0.3 O 0.6 The electronic conductivity is very low, indicating that it is a good ionic conductor.
[0055] Table 1 Summary of test results
[0056]
[0057]
[0058] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A sulfide solid electrolyte co-doped with metal and non-metal elements, characterized in that: The chemical general formula of the sulfide solid electrolyte co-doped with metal and non-metal elements is: Li 10+a-b-c Na b X c M 1-d Q d Te e O f P2S 12-e-f-g Z g , where X is K, Mg, Ca, Al, Fe or Zn; M is one or more of Ge, Sn, Si; Q is at least one of Sb, Bi, As, Y, La; Z is at least one of F, Cl, Br, I; where 0 < b ≤ 3, 0 ≤ c ≤ 1, 0 ≤ d < 1, 0 < e ≤ 2, 0 < f ≤ 1, 0 < g ≤ 3; when the valence of element X is +1, a = 2e + d - g; when the valence of element X is +2, a = 2e + d - c - g; when the valence of element X is +3, a = 2e + d - 2c - g.
2. The metal and non-metal element co-doped sulfide solid electrolyte according to claim 1, characterized in that: The metal and non-metal element co-doped sulfide solid electrolyte is in powder form.
3. The metal and non-metal element co-doped sulfide solid electrolyte according to claim 1, characterized in that: The particle size of the sulfide solid electrolyte co-doped with metal and non-metal elements is 1 nm-100 μm.
4. A method for preparing a sulfide solid electrolyte co-doped with a metal and a non-metallic element as claimed in any one of claims 1 to 3, characterized in that: Under an anhydrous and oxygen-free protective atmosphere, the precursors Li2S, LiZ, Na2S, MTe, XZ x , MS2, QZ3, P2S5, P2O5 are mixed, ball-milled, pelletized by pressing and sintered to obtain a sulfide solid electrolyte Li 10+a-b-c Na b X c M 1-d Q d Te e O f P2S 12-e-f-g Z g , where X is K, Mg, Ca, Al, Fe or Zn; M is one or more of Ge, Sn, Si; Q is at least one of Sb, Bi, As, Y, La; Z is at least one of F, Cl, Br, I; wherein, 0 < b ≤ 3, 0 ≤ c ≤ 1, 0 ≤ d < 1, 0 < e ≤ 2, 0 < f ≤ 1, 0 < g ≤ 3; x is the valence of element X; when x = 1, a = 2e + d - g; when x = 2, a = 2e + d - c - g; when x = 3, a = 2e + d - 2c - g.
5. The preparation method according to claim 4, characterized in that: The protective atmosphere was argon.
6. The preparation method according to claim 4, characterized in that: The ball-to-material mass ratio of the ball mill is 5:1-200:
1.
7. The preparation method according to claim 4, characterized in that: The rotation speed of the ball mill is 100-2000 rpm, and the time of the ball mill is 1-48 hours.
8. An all-solid-state battery, characterized in that: A sulfide solid electrolyte co-doped with a metal and a non-metallic element as described in any one of claims 1 to 3.
Citation Information
Patent Citations
High-entropy inorganic electrolyte material, composite electrolyte material and preparation method thereof
CN113097563A
High-entropy sulfide solid electrolyte material and preparation method and application thereof
CN117039135A
Inorganic sulfide solid electrolyte and preparation method and application thereof
CN117117300A
Modified sulfide solid electrolyte as well as synthesis method and application thereof
CN118645682A
Cited By
Modified sulfide electrolyte and preparation method and application thereof
CN120376732A